Unified approach on the interpretation of piezocone test data in a tropical soil site - Santos, R. A. dos; Rocha, B. P.; Napa-Garcia, G. F.; Giacheti, H. L. [UNESP]; Manzanal, D.; Sfriso, A. O. (Ios Press, 2015)
The unified approach is a semi-empirical method, which incorporated the critical state soil mechanics theory for interpretation of piezocone tests. This paper discuss the applicability of this method to define stratigraphic logging and to estimate geotechnical soil parameters of a typical unsaturated tropical soil site from Brazil. The soil profile at the study site is clayey fine to medium sand with two well-defined layers: Cenozoic sediments overlaying Residual soil from Sandstone. It was concluded that this approach can be used for stratigraphic logging but soil sampling is needed to calibrate soil type. The complexity on the estimative of geotechnical parameters for these unusual soils can be associate to their cohesive-frictional behavior, unsaturated condition and to a possible partially drained condition at the CPTU standard penetration rate. The success of a site investigation will need additional in situ and/or laboratory tests to support geotechnical design on these non-text book soils.
Keywords: Site investigation; in situ test; piezocone; tropical soil; unsaturated soil